The Role of Nizwa University in Spreading the Concept of Knowledge Economy among Students from the Perspectives of Faculty Members Point of View (Journal Of Educational and Psychological Researches, 2022)
The study aims to identify the role of Nizwa University in disseminating the concept of knowledge economy among students from the point of view of the faculty members. The researchers used the descriptive approach, as well as used a questionnaire consisting of (20) items distributed into (4) fields. It was administered to a sample of (93) Faculty members. The results of the study showed that the role of the Nizwa University in spreading the concept of knowledge economy among students from the point of view of the faculty members was of a moderate degree. The education and training field came first with the highest average, while the scientific research and innovation field came in the last level. There were no statistically significant differences attributed to gender. However, there were statistically significant differences attributed to college and teaching experience. The study recommended the necessity of the university presidency and the deanship of scientific research to provide financial support to students in the field of research. In addition, the entrepreneurship center and the deanship of planning should study the needs of the labor market and introduce students to them. Involving students in awareness campaigns, which are directed towards local community institutions.